Nonimaging optics - Winston, Roland (Elsevier Academic Press, 2005)
With nonimaging optics, it's possible to achieve concentrations of solar energy equal to 80,000 suns!
Successor to: High collection nonimaging optics / W.T. Welford, R. Winston.
Keywords: Solar collectors.; Optics.; Reflectors, Lighting.; elektronické knihy; electronic books